Konsep Pendidikan Agama Islam Perspektif Imam Al- Ghazali - Wahidin Wahidin; Asep Rahmatullah (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
According to Al-Ghazali, Islamic education is education that strives to form a perfect human being, both in this world and in the hereafter. According to Al Ghazali, humans can achieve perfection if they are willing to strive to seek knowledge and then practice fadhilah through the knowledge they have learned. According to Al Ghazali, the main goal of Islamic education is to obey Allah the Creator, and the most perfect human being in his view is a human being who always draws closer to Allah. This goal seems to have religious and moral nuances, without ignoring worldly problems. The method used to classify al-Ghazali into two parts: First, the special method of Religious education, this special method of religious education has an orientation towards knowledge of faith because religious education in reality is more difficult than other education, because religious education involves intuitive problems and focuses more on the formation of students' personalities. Second, the special method of moral education, Al-Ghazali said: "Just as a doctor, if he gives his patients only one kind of medicine, will surely kill most of the sick people, so too a teacher, if he shows his students the way with only one kind of practice, will surely destroy their hearts.